1986
DOI: 10.3928/0147-7447-19860301-07
|View full text |Cite
|
Sign up to set email alerts
|

Bateman Bipolar Hip Arthroplasty: A Review of 44 Cases

Abstract: A consecutive series of 71 Bateman hemiarthroplasties were performed in a single hospital over a 20-month period. Forty-four hips or 62% were available for review with an average follow up of 22 months. Of the 44 cases, the Bateman Universal Proximal Femur, original design was used in 40 acute, displaced femora! neck fractures, two failed Austin Moore prostheses, and two cases of femoral head osteonecrosis unassociated with fracture. The mean Harris hip score was 84.7%. Of the patients 93.2% had minimal or no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Probably patients with BHA were judged by the treating surgeons as healthier and more likely to live longer than those receiving UHA, which might have affected the choice of fixation too. 28 In BHA acetabular erosion was theorised to be lessened, as the dual articulation would decrease friction on the cartilage as most of the motion should occur at the metal-onpolyethylene bearing, 31 but this effect has yet to be proven. 29,30 Eiskjaer et al 32 reported on 17 BHA that most of the motion still occurred between the shell and the native acetabulum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probably patients with BHA were judged by the treating surgeons as healthier and more likely to live longer than those receiving UHA, which might have affected the choice of fixation too. 28 In BHA acetabular erosion was theorised to be lessened, as the dual articulation would decrease friction on the cartilage as most of the motion should occur at the metal-onpolyethylene bearing, 31 but this effect has yet to be proven. 29,30 Eiskjaer et al 32 reported on 17 BHA that most of the motion still occurred between the shell and the native acetabulum.…”
Section: Discussionmentioning
confidence: 99%
“…In BHA acetabular erosion was theorised to be lessened, as the dual articulation would decrease friction on the cartilage as most of the motion should occur at the metal-on-polyethylene bearing, 31 but this effect has yet to be proven. 29,30 Eiskjaer et al 32 reported on 17 BHA that most of the motion still occurred between the shell and the native acetabulum.…”
Section: Discussionmentioning
confidence: 99%